Complexity in decision-making - the case of Maasvlakte - Connecting decisions, arenas and actors in spatial decision-making - Marcel Van Gils; Erik-Hans Klijn (European Regional Science Association (ERSA), 2005)
Decision-making about infrastructure is very complex. Decisions to develop the Rotterdam harbour are being taken in a network of local, regional and national actors and influenced by international actors (firms, NGO's etc.) both public and private. This decision-making process shows a lot of uncertainty and complexity and the outcomes are of great importance for the development of the harbour. Network theory has been widely used to indicate, explain and manage uncertainty in decision-making processes. The theory is well equipped for empirical research and has shown many applicable results. The attention for influences from outside the network to decision-making inside the network is however still poorly developed. In the case of decision-making with a strong international component this is a handicap. In this paper the relation between influences from outside and decision-making inside networks is studied both theoretically and empirically. A distinction is made between locally bound and non-locally bound networks to theorise the complex decision-making process. The well-known scientific concept of space of flows versus space of places from Manuel Castells is used as an inspiration to describe the relation between the locally and non-locally bounded networks of decision making. The locally bounded network is formed by the formal decision making process between the governmental and non-governmental organisations in countries, regions and municipalities. The non-locally bounded networks exist of organizations that are footloose and act globally mainly according to economic principals. The concept of inclusion is used to analyse the various actors in the decision-making process. The paper starts with the description of the external influences in port areas in general. The balance between the influence of local and non-local bounded networks depends on the multiple-inclusion of the different actors in the decision-making process in both networks. In areas in which many actors are included in the place-bounded networks, the external influences can be expected to be marginal. The port area of Rotterdam is a node in international networks and so the hypothesis can be set that in the Rotterdam port area the influence of actors mainly included in non-place bounded networks is significant in decision making networks. To explore this assumption various networks, which are relevant for decision-making about spatial issues in the Rotterdam port are identified and the differences in inclusion of the relevant actors is analysed. By means of the analysis of perceptions of the various actors (locally bound or non-locally bound) and their strategic choices and decisions we show that notions on international port development are being interpreted and transformed quite differently by the various actors. This first part of analysis highlights the possible gap between the awareness of the various actors of the non-locally bounded networks and their translation into their strategies in local bounded networks. We also trace difference of perceptions and strategies between actors who solely operate in locally bound networks and actors who are both included in locally and non-locally bound networks (like shipping firms etc). This second part of analysis indicates if there are differences in what the actors use as input for their respective positions in the decision-making networks. The paper shows that the influence of external developments in non-locally bound networks manifests itself in locally bound networks but is transformed and interpreted in many ways by the different actors. The paper ends with some conclusions about decision-making on large ports and the possibilities to influence this complex decision-making process that takes place in locally bound and non-locally bounded networks at the same time.
Keywords: 330